Pericarditis as the Main Clinical Manifestation of COVID-19 in Adolescents. Issue 5 (12th April 2021) - Dimopoulou, Dimitra; Spyridis, Nikolaos; Dasoula, Foteini; Krepis, Panagiotis; Eleftheriou, Eirini; Liaska, Marianthi; Servos, Giorgos; Maritsi, Despoina; Tsolia, Maria
Abstract : Supplemental Digital Content is available in the text. Abstract : Children and adolescents with severe acute respiratory syndrome coronavirus 2 infection usually have a milder illness, lower mortality rates and may manifest different clinical entities compared with adults. Acute effusive pericarditis is a rare clinical manifestation in patients with COVID-19, especially among those without concurrent pulmonary disease or myocardial injury. We present 2 cases of acute pericarditis, in the absence of initial respiratory or other symptoms, in adolescents with COVID-19.